Tahqiq ma'na al Sunnah wa bayan al hajati ilayha : dirasah ilmiyyah nafisat li kabir 'ulama' Musliy al Hindi al Sayyid Sulayman al Nadwi - Sayyid Muhammad Rashid Rida (Al Maktabah al Islamiy, 1994)
ws.c.1